Indicadores de monitoramento e de avaliação dos serviços de saúde em hanseníase em uma capital hiperendêmica do nordeste brasileiro - MAGALHÃES, Camila Castro (2022)
INTRODUCTION: Leprosy is a disease of great relevance to public health due to its magnitude and high disabling power, reaching mainly the economically active age group, requiring effective actions for its control. The evaluation of progress in the elimination of leprosy is extremely important because it is a priority problem in Brazil's health policy and the use of adequate indicators makes it possible to plan actions for services directly impacting their quality. OBJECTIVE: To analyze the monitoring and evaluation indicators of leprosy services from 2015 to 2020 in the city of São Luís, Maranhão. MATERIAL AND METHOD: This is an evaluative descriptive study with a quantitative approach and secondary data that is part of the larger project entitled “INTEGRAHANS MARANHÃO: integrated approach to clinical, epidemiological (spatial-temporal), operational and psychosocial aspects of leprosy in a hyperendemic city in Maranhão”. The population consisted of all new cases of leprosy notified by the city of São Luís, in the period from 2015 to 2020, excluding cases closed as a diagnostic error. Data for indicators were collected from the state database of SINAN and refer to cases of leprosy notified in the defined time frame and the demographic data relative to the annual population were based on IBGE. To analyze the monitoring and evaluation indicators of leprosy services, we used the parameters recommended by the Ministry of Health. RESULTS: It was found that the city of São Luís is hyperendemic for leprosy and that the health services have weaknesses in the actions developed for control of leprosy, both in timely detection and in the follow-up of cases, and in the surveillance of contacts.